Community structure of periphyton on bamboo substrate in whiteleg shrimp (Litopenaeus vannamei Boone, 1931) pond with semi-biofloc system - DIANA ARFIATI; UMI ZAKIYAH; SEPTI ANITASARI; ZAKIYYAH NUR INAYAH; RIZKY KUSMA PRATIWI (Society for Indonesian Biodiversity, 2023)
Abstract. Arfiati D, Zakiyah U, Anitasari S, Inayah ZN, Pratiwi RK. 2023. Community structure of periphyton on bamboo substrate in whiteleg shrimp (Litopenaeus vannamei Boone, 1931) pond with semi-biofloc system. Biodiversitas 24: 5080-5087. Periphyton is one aquatic organism that attaches to the substrate and can be used as a bioindicator. This study analyzes the community structure and dynamics of periphyton on bamboo substrates in whiteleg shrimp ponds with a semi-biofloc system. The study was conducted from May to July 2022. The bamboo substrate was placed in the ponds, and the samples were taken every seven days to 8 weeks. Identification and calculation of periphyton using Lackey Drop Micro transect Counting Method. The periphyton was found on a bamboo substrate in whiteleg shrimp ponds with a semi-biofloc system consisting of phyto-periphyton and zoo-periphyton. The phyto-periphyton group contains 4 phylum, 21 species, including the Bacillariophyta, Chlorophyta, Cyanophyta, and Ocrophyta. The zoo-periphyton group has 4 phylum, 10 species consisting of Arthropoda, Ciliophora, Nematoda, and Rotifera. The abundance of periphyton found changes every week. The relative abundance of phyto-periphyton includes phylum Bacillariophyta (17-69%), Chlorophyta (1-22%), Cyanophyta (30-65%), and Ocrophyta (0-25%), while zoo-periphyton includes phylum Arthropoda (0-3%), Ciliophora (69-99%), Nematodes (0-2%) and Rotifers (0-28%). The total abundance of phyto-periphyton on bamboo substrate ranged from 223,806-989,398 cells/L, while zoo-periphyton ranged from 396-1,924 individual/L. The diversity, uniformity, and dominance index of phyto-periphyton and zoo-periphyton are moderate. Water quality parameters during the study were relatively good for aquatic organism growth, except for very high total organic matter levels in several weeks.